An accelerated LIF neuronal network array for a large-scale mixed-signal neuromorphic architecture - Aamir, Syed Ahmed; Stradmann, Yannik; Müller, Paul; Pehle, Christian; Hartel, Andreas; Grübl, Andreas; Schemmel, Johannes; Meier, Karlheinz (IEEE transactions on biomedical circuits and systems, 2018)
We present an array of leaky integrate-and-fire (LIF) neuron circuits designed for the second-generation BrainScaleS mixed-signal 65-nm CMOS neuromorphic hardware. The neuronal array is embedded in the analog network core of a scaled-down prototype high input count analog neural network with digital learning system chip. Designed as continuous-time circuits, the neurons are highly tunable and reconfigurable elements with accelerated dynamics. Each neuron integrates input current from a multitude of incoming synapses and evokes a digital spike event output. The circuit offers a wide tuning range for synaptic and membrane time constants, as well as for refractory periods to cover a number of computational models. We elucidate our design methodology, underlying circuit design, calibration, and measurement results from individual sub-circuits across multiple dies. The circuit dynamics matches with the behavior of the LIF mathematical model. We further demonstrate a winner-take-all network on the prototype chip as a typical element of cortical processing.